Properties of modified sand brick using bagasse - Nurul 'Afifah Yazid (School of Environmental Engineering, University Malaysia Perlis, 2012)
An extensive variety of such additional materials from waste has been used or investigates in brick making to improve the brick production whether in their costs, manufacture handling, strengths, and other major properties indeed. In this study, agricultural waste bagasse was chose as material in investigating the properties of the modified sand brick. Bagasse or sugarcane bagasse is the fibrous matter that remains after sugarcane stalks are crushed to extract their juice. The main aims and objectives in this study is to study the chemical compositions in bagasse as cement replacement and determine the physical and engineering properties of the modified sand brick using bagasse while to investigates the difference between normal sand brick and modified sand brick using bagasse. Brick samples with 10%, 15%, and 20% bagasse as cement replacement were prepared and tested for physical and engineering properties. The bricks colour, texture, and density were determined to obtain the physical properties while its compressive strength and water absorption were measured for engineering properties. It was found that all of the bricks sample which is bricks with 10%, 15% and 20% of bagasse as cement replacement can be acceptable as Non-load Bearing Concrete Masonry Unit as their values of compressive strength at the 28th days are all still higher than the minimum requirement which is 4.14 MPa while the bricks water absorption are increased and its density are decreased as the usage of bagasse as cement replacement increased in modified sand brick production.